Occurrence and Consequences of Coding Sequence Insertions and Deletions in Mammalian Genomes - Taylor, Martin S.; Ponting, Chris P.; Copley, Richard R.

(untitled) (Genome Research, 2004)
Nucleotide insertion and deletion (indel) events, together with substitutions, represent the major mutational processes of gene evolution. Through the alignment of 8148 orthologous genes from human, mouse, and rat, we have identified 1743 indel events within rodent protein-coding sequences. Using human as an out-group, we reconstructed the mutational event underlying each of these indels. Overall, we found an excess of deletions over insertions, particularly for the rat lineage (70% excess). Sequence slippage accounts for at least 52% of insertions and 38% of deletions. We have also evaluated the selective tolerance of identifiable protein structures to indels. Transmembrane domains are the least, and low complexity regions, the most tolerant. Mapping of indels onto known protein structures demonstrated that structural cores are markedly less tolerant to indels than are loop regions. There is a specific enrichment of CpG dinucleotides in close proximity to insertion events, and both insertions and deletions are more common in higher G+C content sequences.